Health Disparities in Uterine Cancer: Report From the Uterine Cancer Evidence Review Conference. Issue 8 (August 2022) - Whetstone, Sara; Burke, William; Sheth, Sangini S.; Brooks, Rebecca; Cavens, Arjeme; Huber-Keener, Kathryn; Scott, Dana M.; Worly, Brett; Chelmow, David
Abstract : (Abstracted from Obstet Gynecol 2022;139:645–659) The American College of Obstetricians and Gynecologists (ACOG) convened a panel of experts to develop evidence-based educational materials for clinicians on health disparities in the treatment, diagnosis, and outcomes for uterine cancer. Based on reviews of the literature, best practices, and guidelines, the panel identified substantive inequities and provided guidance for future research.